Pressure-tuning of the magnetic properties of the Heusler compound Mn2PtGa - Mejia, C. Salazar; Nayak, A. K.; Felser, Claudia; Nicklas, Michael (Journal of Applied Physics, 2018)
We report on the pressure-tuning of the magnetic properties of the Heusler alloy Mn 2PtGa. At ambient pressure, Mn 2PtGa orders ferrimagnetically below T C ≈ 222 K, followed by a first-order ferrimagnetic to antiferromagnetic transition around T FI - AF ≈ 102 K upon cooling. Magnetization measurements up to 1.2 GPa evidence a stabilization of the ferrimagnetic phase, i.e., T C increases while T FI - AF decreases upon application of pressure. The magnetic properties in the ferrimagnetic phase are not altered upon increasing pressure. However, the fraction of the ferrimagnetic phase present in the inhomogeneous antiferromagnetic low-temperature phase increases with pressure.
CRIS-Team Scopus Importer:2022-04-14